Examining Savvy Salespeople Practicing Entrepreneurship And Client-Oriented Selling To Enhance Cross-Border Sales - Widiastono, Hubert; Rahman, Fathony; Yosevina, Christiana (International Research Journal of Business Studies, 2023)
Organizational marketing, sometimes referred to as business-to-business (B2B) marketing, typically deals with a limited clientele, resulting in a close relationship between customers and salespeople. The link must be managed carefully for the salesmen to employ entrepreneurial strategies to increase clients’ readiness to repurchase products and ultimately meet the company’s sales target, especially for those working in international markets. However, no well-validated model has been developed to demonstrate that salespeople who engage in corporate entrepreneurship and client-focused sales of the company do better in cross-border sales. The goal of the study is to test and validate a conceptual model that claims salespeople who engage in corporate entrepreneurship and client-centered selling perform better in cross-border sales when the company has a high capacity for absorption. Data analysis was done as part of the quantitative research method utilized in this study.